On n-A-con-cos Groups and Determination of some 3-A-con-cos Groups - Ahmad Gholami; Fatemeh Mahmudi (Mathematics Interdisciplinary Research, 2021)
In this paper, we introduce the concept of n-A-con-cos groups, n ≥ 2, mention some properties of them and determine all finite abelian groups with at most two direct factors. As a consequence, it is proved that dihedral groups D2m in which m has at most two prime factors are n-A-con-cos.